2012
DOI: 10.2139/ssrn.2102459
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and Food Security in Asia by 2030

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In the more densely populated economies of the region, the growth in labor-intensive and manufactured component exports will be accompanied by rapid increases in the per capita incomes of low-skilled workers (Baldwin 2011). Agricultural comparative advantage is thus likely to decline in these economies (Anderson and Strutt 2012). Whether these economies become more dependent on imports of farm products, however, depends on what happens to their RRAs.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In the more densely populated economies of the region, the growth in labor-intensive and manufactured component exports will be accompanied by rapid increases in the per capita incomes of low-skilled workers (Baldwin 2011). Agricultural comparative advantage is thus likely to decline in these economies (Anderson and Strutt 2012). Whether these economies become more dependent on imports of farm products, however, depends on what happens to their RRAs.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Over the 20-year horizon of our analysis, this would mean that agricultural prices would rise by 93% instead of 30% in the baseline solution. Experts disagree on how agricultural prices are likely to evolve; some supporting an upward drift of prices (McKinsey Global Institute 2011), but others are more optimistic that long-term trends in productivity increases will resume and offset demand pressures (Anderson and Strutt 2011).…”
Section: Structural Shocks and Policy Alternativesmentioning
confidence: 99%
“…By and large, these studies find that trade liberalization facilitates food security by increasing income, reducing poverty, reducing price volatility, making food cheaper, or simply making food physically available. Using computable general equilibrium analysis, Anderson and Strutt (2012) predict that the liberalization of global agricultural trade will increase world GDP, with most of the gains accruing to Association of Southeast Asian Nations (ASEAN) and Pacific island countries. They also found that liberalization leads to increases in agriculture sector total factor productivity, confirming the results of an earlier study by Martin and Mitra (2001), which used a production function framework to show that productivity increases in the agriculture sector are supportive of growth.…”
Section: Mapping Food Tradementioning
confidence: 99%
“…On the other hand, a self-reliant emphasis on availability sees trade as a potential tool for making food cheaper and more widely accessible. As Anderson and Strutt (2012) note, self-sufficiency emphasizes production, while availability serves consumption. Governments in Asia, at least in rhetoric, tenaciously hold on to the selfsufficiency mantra while economists tend toward self-reliance.…”
Section: Introductionmentioning
confidence: 99%